Анализ чувствительности диагностических моделей для контроля состояния обмоток трансформатора под нагрузкой - Беляев, В.К.; Ободовский, В.Д.; Паненко, Е.Н. (Технічна електродинаміка, 2013)
Описана методика определения характеристик качества линейных диагностических моделей контроля деформаций обмоток силового трансформатора, построенных на основе системы уравнений общей теории трансформаторов. Получены выражения для расчета коэффициентов чувствительности и погрешности моделей, используемых для оценки модуля сопротивления обмоток. Определены особенности влияния погрешностей измерения напряжений, токов, углов фаз на погрешность моделей при разных режимах работы трансформатора, близких к номинальному. Описано метод дослідження характеристик якості лінійних діагностичних моделей контролю деформації обмоток силового трансформатора, побудованих на основі рівнянь загальної теорії трансформаторів. Отримано вирази для визначення коефіцієнтів чутливості і похибок моделей, які використовують для оцінки модуля опору обмоток. Визначено особливості впливу похибок виміру напруг, струмів, кутів фаз на похибки моделей при режимах роботи трансформатора, близьких до номінального The technique of definition of characteristics of quality of linear diagnostic models which are used in on–line monitoring systems of condition of power transformer windings by windings resistance measurement is presented. Such diagnostic models are analyzed: model based on simple use of equations system of the general theory of transformers, model with regularization of equations system and the simplified model. Expressions for calculation of sensitivity factors and a lapse of the observed models are gained. Agency features of measuring errors of voltages, currents, angles of phases, on a lapse of the diagnostic models are defined at transformer operation modes which are close to the nominal. It is shown that, using the gained expressions of sensitivity factors and a lapse it is possible to gain necessary accuracy of techniques and the measurement equipment and also to define parameters of an optimum transformer operating mode, which are used at the monitoring of a windings condition with application of the observed models.